Safeguards and antidumping in Latin American trade liberalization : (World Bank, 2006)
Until the 1990s, the main users of safeguards and antidumping laws were Australia, Canada, the European Union, and the United States. Since then, many countries have implemented such laws, leading to a proliferation in antidumping and safeguard activity across the world. This timely book documents the political economy surrounding the implementation of these laws in seven Latin American countries and provides details on the institutions created, implementation of the laws, and subsequent activity. It finds that, in the larger political context, antidumping and safeguards are a necessary quid p.